Effect of individual counselling on psychological distress among victims of domestic violence in Negeri Sembilan, Malaysia - P.C.Hermangild, Deborah Priya (2021)
Domestic violence is a global phenomenon and does not discriminate against race, age, culture, and gender. This study was conducted to better understand the effect of individual counselling on psychological distress among victims of domestic violence. The study also explored the differences in psychological distress levels among the two groups of domestic violence victims at baseline and three months follow-up. The research design used a pre-and post-test quasi-experimental design to study the relationship between the variables among victims of domestic violence in Negeri Sembilan, Malaysia. The data was collected and analysed using both descriptive and inferential statistics. Participants comprised of 58 domestic violence women victims from eight districts within Negeri Sembilan. They were recruited using a nonprobability sampling method, specifically purposive sampling, where victims of domestic violence who lodged a police report between the months of September 2018 to March 2019 were referred to the Victim Care Centre and were included in the study. The Victim Care Centre is a division under the Criminal Investigation Department of the Royal Malaysian Police that provides psychological and counselling services to victims of crimes through their professionally trained and Victim Care Officers. In addition to a sociodemographic questionnaire, the following Bahasa Melayu translated versions of instruments were used: Beck Depression Inventory (Cronbach‘s α: 0.91), Beck Anxiety Inventory (Cronbach‘s α: 0.91) and Brief Coping Orientation to Problems Experienced (Cronbach‘s α: 0.83) to measure the variables of the study. There was an equal proportion of participants who accepted counselling (n=29, 50%) compared to those who did not accept counselling (n=29, 50%). Findings showed that there were no significant differences between domestic violence victims who accepted counselling and those who did not accept counselling in terms of sociodemographic factors (age, race, income, education, number of children) except for the duration of abuse. In terms of coping mechanism, both groups appeared to favour the utilization of an approach coping mechanism (n=41, 70.69 %) compared to an avoidant coping mechanism (n=10, 17.24 %). There was also a significant reduction in the participant‘s symptoms of depression (accepted counselling: t (28) = 3.715, p = .001, did not accept counselling: t (28) = 3.706, p = .001) and anxiety (accepted counselling: t (28) = 4.827, p = .001, did not accept counselling: t (28) = 3.604, p = .001) between the baseline and three months follow-up. There is a need to examine ways to increase counselling acceptance rates which could be possibly achieved by increasing awareness and promotion of services. This study carries shared insight into counselling acceptance rates among domestic violence victims in a Victim Care Centre in Negeri Sembilan. Future studies should be expanded to Victim Care Centres in other states to obtain more representative information on the effectiveness of the counselling services provided to domestic violence victims.